Using surface water games to engage communities in water management in Odisha, India - Melesse, Mequanint B.; Duche, Vishwambhar; Guvvalavenkata, Anupama; Kumar, Dron; Sanil, Richu; Falk, Thomas; Meinzen-Dick, Ruth S. (CGIAR System Organization, 2024)
In November 2024, more than 110 practitioners from government, NGOs, and the private sector in Odisha, India, shared their experiences on integrating surface water games into their water management toolkits. There were several benefits but the main message was that the game provided a mechanism for raising community awareness on water as a valuable common resource.